POVERTY REDUCTION PUBLIC POLICY: A STUDY ON THE IMPLEMENTATION OF THE SMART INDONESIA PROGRAM IN KONAWE DISTRICT - Edy Tadung; Muh Idul Triawan (Universitas Negeri Yogyakarta, 2022)
This article reviews the public policy of the Smart Indonesia Program. Qualitative research approach with descriptive method. The data were processed by in-depth interviews, observations and document review. The data were analyzed descriptively with a phenemological case study. The results of the study show that as a public policy, the Smart Indonesia program is able to alleviate poverty in the field of education for the poor with the cooperation of related parties and equalization of education for students in Konawe Regency. The implementation of the Smart Indonesia Program was analyzed in terms of the dimensions of communication, resources, disposition and bureaucratic structure. Program effectiveness needs to be determined by the program monitoring team. The school continues to proactively carry out monitoring, evaluation and guidance as well as to parents and recipient students so that the program funds used are targeted and effective in assisting student education.